AVAILABILITY AND UTILIZATION OF E-COUNSELLING PLATFORMS FOR QUALITY DISTANCE LEARNING IN NATIONAL OPEN UNIVERSITY OF NIGERIA - Ukwueze, Augustine C. (Indonesian Journal of Learning and Instruction, 2018)
The emergence of technology has made it possible for counsellors all over the world to reach their clients in distant locations without compromising the principle of confidentiality. This study examined the availability and utilization of e-counselling platforms in counselling students for quality distance learning in the National Open University of Nigeria (NOUN). Through purposive research design using 56 professional counsellors in the university, five research questions and two hypotheses were formulated to guide the study. Data collection was through a self-structured questionnaire that sought information from the respondents on the availability, utilization, challenges and possible solutions to e-counselling platforms in NOUN. Both descriptive and inferential statistical tools were used to analyse the data using the SPSS platform. The results of the study showed that most of the modern social media platforms for e-counselling are not available for use in the university. In effect, there are challenges that face the utilization of e-counselling platforms, which include inadequate power supply and lack of ICT facilities. The study recommended the provision of alternative power supply, free data for students and counsellors as well as computerized counselling laboratories with internet connections for students and counsellors in all the study centres of the university.Keywords: availability; utilization; e-counselling; distance learning.